Automatic Monitoring and Controlled Atmosphere System Using Arduino on Tropical Fruit Container Integrated with IoT - Alam Baheramsyah; Khitoh Fatahilah (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2021)
Indonesia is a tropical country that is gifted with various kinds of abundant natural resources. Among them are exotic fruits which are in great demand by other people in the world. Meanwhile, in the delivery and storage process for distribution, technology that can maintain the resilience of the fruit is needed so that it does not ripen quickly, thereby increasing its economic value. From this problem, a device called Controlled Atmosphere Storage (CAS) was created which could store fruit and adjust its room conditions according to the specific air requirements of each commodity in the container. The control system design in this study aims to determine how to regulate the levels of ethylene, oxygen, carbon dioxide, and temperature by using the Arduino Uno as a microcontroller and integrating it with the IoT system. The system consists of a microcontroller, DHT22 sensor, MQ 135 sensor, MQ5 sensor, KE25 sensor, relay, Esp8266, and actuators such as fans and servo. From the experimental results, it is known that the control system used is capable of conducting air conditioning in the container and can integrate it with the IoT concept using Thingspeak.com media.